Design of an Information System for Archiving Hajj Pilgrim Files at the Ministry of Religion of Medan City - Irma Listiani; Yustria Handika Siregar (Bigint Computing Journal, 2024)
In the era of globalization, computer technology plays a very important role in assisting the process of activities at the Medan City Ministry of Religion office, especially in the Hajj services section where files are still stored manually. The aim of creating this file filing system is to help and make it easier for employees to manage existing files.The research process involved identifying problems in Hajj file management, collecting data through observation, interviews, and literature study. System development uses PHP, Bootstrap, and HTML5 programming languages ​​as well as software, MySQL, Xampp, and Visual Studio Code. This system development method uses the waterfall method which has stages in a systematic sequence starting from analysis to maintenance. This research produces an information system in the form of a file archiving website that can help employees work in storing files, searching for data quickly and accurately, minimizing the risk of damage or loss of files, as well as making it easier for employees to manage archive data to be more effective and efficient, as well as ensuring information security stored data.